Academic Globalization: Where Did We Come from? Where Are We Going? - Altbach, Philip; Salmi, Jamil (International Higher Education, 2022)
Almost all existing universities stem from the Western university model. This article discusses this tradition—how colonialism impacted the expansion of universities and the reasons why modern universities continue to use this pattern of academic development.